Prevalence of hypothyroidism and its epidemiological parameters among the adults in selected urban areas of Amritsar - Kaur, Akashpreet; Kaur, Manpreet; Mohan, Gurinder (International Journal Of Community Medicine And Public Health, 2025)
Background: The endocrine system plays a vital role in orchestrating cellular interactions, metabolism, growth and senescence. The prevalence of hypothyroidism in the developed world is about 4-5% and subclinical hypothyroidism is 4-15%. Hypothyroidism is the most common of thyroid disorders in India, affecting one in ten adults. Although millions of men experience thyroid dysfunction, women are 10 times more likely to have a thyroid imbalance. Methods: A descriptive longitudinal study was adopted among 800 adults residing at Kitta, a community area under SGRDUHS. Data was collected from adults (Baseline datasheet, clinical variables, dietary and lifestyle characteristics) through simple random sampling. Thyroid screening was done using Zulewski clinical score of hypothyroidisms. Results: The present study findings revealed overall prevalence of hypothyroidism as 9.3%. Using regression analysis, various epidemiological parameters of hypothyroidism were identified i.e., age, gender, usage of salt etc was found highly significant at p<0.05 level of significance. Conclusions: The prevalence of hypothyroidism was high, affecting approximately 9.3% of adults in the study population. Epidemiological parameters like age, female gender etc were identified in hypothyroidism.